Assessment of energy savings by mechanical system retrofit of existing buildings. (2017) - Wang, Haidong; Xue, Yuantao; Mu, Yu
Abstract: This paper summarizes most commonly used measures of air conditioning system energy saving retrofit, discusses the methods of energy saving calculation using utility data of pre-retrofit and post-retrofit periods and demonstrates it by a retro-commissioning project of a health center in Dallas, Texas, US. Regression models were established based on the average outdoor temperature and the degree-day to rule out the effect of weather difference. Energy consumption (adjust) of pro-retrofit period is obtained from the regression model. Energy saving is calculated by energy consumption (adjust) of pro-retrofit period minus energy consumption of post-retrofit period. Results show that electricity and gas energy saving percentages are greater than 10% calculated by different energy saving calculation methods. These commonly used energy saving measures can effectively reduce the building energy consumption and energy efficiency assessment methods can reflect the energy-saving effect.